Assessment policies and academic progress: differences in performance and selection for progress. Issue 7 (3rd October 2021) - Kickert, Rob; Meeuwisse, Marieke; Arends, Lidia R.; Prinzie, Peter; Stegers-Jager, Karen M.
Abstract: Despite the benefits swift academic progress holds for many stakeholders, there is scarce literature on how academic progress may be improved by changes to assessment policies. Therefore, we investigated academic progress of first-year students after an alteration of characteristics of the assessment policies in three large course programmes: business administration ( n  = 2048) changed the stakes; medicine ( n  = 1630) changed the stakes and performance standard; psychology ( n  = 1076) changed the stakes, performance standard and resit standard. Results indicate that students' academic progress was sensitive to the characteristics of the assessment policy in all three course programmes. The changes in progress could be explained by differences in performance, as well as by differences in selection for progress by the different policies. Implications are that assessment policies seem effective in shaping student progress, although one size does not fit all.